Decolonising higher education research: From a uni-versity to a pluri-versity of approaches - Martinez-Vargas, C. (South African Journal of Higher Education, 2020)
Decolonial rhetoric has enveloped the South African academic world advocating for cognitive justice. Debates have increased exponentially, highlighting the complexities of the theme and the diversity of positionalities towards a decolonial solution. Thus, the imperative responsibility to explore the debates and participate in the active networks towards a partial solution has become clear. Therefore, this article explores the decolonial literature. It introduces the complexities of the epistemological field and upholds a pluri-versity of approaches. In this university converted into a pluri-versity, practices should be diverse in form and content, including knowledge systems historically excluded, but equally preserve those that, although imposed, should still be present for an ecology of knowledges. To do so, I argue that despite the use of African or indigenous methodologies being used as a way to decolonise research, we need to increase the use of participatory methodologies, in their diverse forms. Thus, diversifying our practices as researchers and combining them with traditional research practices is the only way to promote a pluriverse which is nurtured by diverse knowledge systems on our way towards decolonisation.